(untitled) (Journal of Chemical Engineering, 2014)
This study focused on the generation of electricity from whey in a bio-fuel cell (BFC). Whey or Milk Serum is the liquid remaining after milk has been curdled and strained. It is a by-product of the manufacture of cheese or casein in Foods and Sweets Company. It was selected as electrolyte in biofuel cell due to containing higher amount of branched-chain amino acids (BCAA’s).The pH value of fresh whey was 3.1-3.8. Three categories of whey were used in the experiments included fresh whey, preserved by thermal treatment and preserved with 2% phenol by volume. It was observed that microorganism growth was zero in the sample with 2% phenol and growth rate was medium in the sample preserved by thermal treatment and that was higher in the fresh sample. In this biofuel cell, voltage was increased with the increase of surface area of electrodes. For a single compartment containing 8 unit cells, resultant voltage and current were 2.86V and 450?A and four compartment 32 unit cells in series, the values were 10.90V and 8.05mA respectively. When anode area was increased to reduce polarization, power generation was initially high but the decreasing rate of power was also elevated. Finally, for commercial electrodes, maximum power and minimum internal resistance were recorded. The maximum Current, Voltage and Power for commercial electrodes in a single compartment containing 10 unit cells were 78mA, 3.88V and 0.30264W respectively. DOI: http://dx.doi.org/10.3329/jce.v28i1.18105 Journal of Chemical Engineering, Vol. 28, No. 1, December 2013: 22-26